Single-layer graphene saturable absorber for diode-pumped passively Q-switched Tm:KLu(WO4)2 laser at 2 μm. (29th July 2015) - Serres, Josep M; Mateos, Xavier; Griebner, Uwe; Petrov, Valentin; Aguiló, Magdalena; Díaz, Francesc
Abstract: We demonstrate a diode-pumped passively Q-switched Tm-laser emitting near 2 μ m using single-layer graphene as the saturable absorber. The commercially available graphene samples were characterized by Raman spectroscopy and pump–probe measurements indicating high quality layered graphene. The Q-switched Tm:KLuW laser generated maximum pulse energy of 1 μ J with a slope efficiency of 11%. The maximum average output power was 34 mW at a repetition rate of 35 kHz.